Orientalism in the Kite Runner Novel by Khaled Hosseini - Tommi Pungkaswani; Merry Rullyanti; Dhanu Ario Putra (Literary Criticism, 2021)
Nowadays there are some countries still get interference and new colonialism style from other countries that have more power, it has happened since long time ago until now, especially Asia dan Africa countries. This thesis analyzes orientalism in The Kite Runner novel by Khaled Hosseini. This study intends to show their superior and inferior as The West and The Eas4 and the effects of orientalism in the novel The Kite Runner. The story happened when Russia attacked Afghanistan. This thesis used descriptive qualitative method that consist of collecting data, analyzing data, and presenting the data. In this study, the researcher used Orientalism theory by Edward Said. In this thesis the researcher analyzes selected novel The Kite Runner (2013) by Khaled Hosseini. The researcher finds some samples that shows in the novel there are part about The West, The East, and effects of orientalism. The West according to the novel are Assef and Russia because they delegated side that had more power to oppress weak side/ The East. The East according to the novel are Hassan and Afghanistan because they delegated side that had less power and get oppressed by strong side/ The West. The effects of orientalism during and after the war and conflict are Afghanistan became the country that had many problem like rubber, beggar, poverty, suffering and fear. Keyword: Orientalism, The West, The East, Superior, Inferior